Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Please help me solve this question unable to do it...

Please help me solve this question unable to do it...

Question Image
Grade:12

1 Answers

Aditya Gupta
2080 Points
one year ago
differentiate both sides we get
f(x)sinxcosx= f’(x)/[2(b^2 – a^2)f(x)] where we have used chain rule to diff lnf(x).
let y= f(x) so that
dy/dx= 2(b^2 – a^2)*y^2sinxcosx
or dy/y^2= (b^2 – a^2)*2sinxcosx dx
integrate both sides
 – 1/y= 2(b^2 – a^2)*sin^2x + c
or y= 1/[(a^2 – b^2)*sin^2x – c] where c is any constant.
if we let c= – b^2, then
y= 1/[(a^2sin^2x + b^2(1 – sin^2x)]
or y= f(x)= 1/(a^2sin^2x + b^2cos^2x)
KINDLY APPROVE :))

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free